Treatment of segmental tibial defects using acute bone shortening followed by gradual lengthening with circular external fixator - Rahal, Sheila Canevese [UNESP]; Volpi, R. S.; Vulcano, Luiz Carlos [UNESP] (Blackwell Verlag Gmbh, 2005)
The aim of this study was to clinically and radiographically evaluate acute bone shortening followed by gradual lengthening in the treatment of large segmental tibia defects induced in seven clinically normal dogs. A circular external fixator was assembled with one proximal 5/8-circle ring, one middle ring and one distal ring connected with three rods. Thirty per cent of the tibia and fibula were removed in the middle and distal parts of the diaphyses, between the middle and distal rings. Acute bone shortening with compression of proximal and distal segments was performed. A subperiosteal osteotomy was performed between the half-ring and middle ring. Bone distraction started 7 days after surgery; after lengthening, the apparatus was left in place for 14 weeks for consolidation of regenerated bone. The frame was removed at the end of this period, and the dogs observed for four more weeks. Functional results were considered excellent in two, good in three and fair in the other two dogs. Bone regeneration within the distraction gap was obtained 14 weeks after neutral fixation period. We concluded that acute bone shortening followed by gradual lengthening by Ilizarov method can be used to treat extensive tibial defects in dogs, although it presents limb temporary abnormal limb shape and unequal length as early disadvantages.